2021
DOI: 10.3329/brj.v24i1.53240
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Genotype × Environment Interaction for Identification of Stable Genotypes to Grain Yield of Rice (Oryza sativa L.) Varieties in Bangladesh Rainfed Condition

Abstract: The research was evaluated in seven ecological zones throughout the country following randomized complete block design with three replications in each location. The combined analysis of variance for grain yield indicated that the differences among all sources of variation were highly significant (P<0.01). Environment (E), Genotype (G) and G × E interaction effects explained by 25.54%, 17.02% and 48.97% for inbred and 35.26%, 17.03%, 31.23% for hybrid of the total sum of square, respectively. Locations E2 (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Incomparable to Forat1 variety which showed a response to favorable environments for the traits of the number of days to flowering 50%, the weight of 1000 grains and grain yield, while being responsive to poor environments for the panicle length trait, and an unstable response to environmental conditions for the rest of the traits. Besides, the Anber33 variety showed the lowest grain yield (4.563 ton.ha -1 ) by responding to suitable environments for the two traits (weight of 1000 grains and grain yield) and it has responded to unfavorable environments for the panicle length, also it is difficult to predict linearly for the rest of the traits (Meena et al, 2016;Kumar et al, 2020;Debsharma et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Incomparable to Forat1 variety which showed a response to favorable environments for the traits of the number of days to flowering 50%, the weight of 1000 grains and grain yield, while being responsive to poor environments for the panicle length trait, and an unstable response to environmental conditions for the rest of the traits. Besides, the Anber33 variety showed the lowest grain yield (4.563 ton.ha -1 ) by responding to suitable environments for the two traits (weight of 1000 grains and grain yield) and it has responded to unfavorable environments for the panicle length, also it is difficult to predict linearly for the rest of the traits (Meena et al, 2016;Kumar et al, 2020;Debsharma et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The other winner genotypes G5 (IR87872-7-1-1-2-1-B) and G9 (BR8980-B-1-3-5) make up another mega-environment. Also, the genotype in the polygon (for example G3, G6, and G13 for Mega-E1) was less sensitive to the location than the winning genotype [ 45 , 57 ]. The two other corner genotypes, G5 and G9, were low-yielding ( Fig 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The AMMI results showed that genotypic effects, followed by GEI effects and environmental impacts, contributed the most. The higher value in IPCA 1 and IPCA 2 was enough to analyze the whole G-E interaction [43][44][45]. The existence of a substantial percentage of LGI dictates the analysis of the stability of elite rice genotypes over locations.…”
Section: Plos Onementioning
confidence: 99%